A Scalable Approach to High-Impact Tutoring for Young Readers: Results of a Randomized Controlled Trial - Kalena E. Cortes; Karen Kortecamp; Susanna Loeb; Carly D. Robinson (Institute of Labor Economics (IZA), 2024)
This paper presents the results from a randomized controlled trial of Chapter One, an early elementary reading tutoring program that embeds part-time tutors into the classroom to provide short bursts of 1:1 instruction. Eligible kindergarten students were randomly assigned to receive supplementary tutoring during the 2021-22 school year (N=818). The study occurred in a large Southeastern district serving predominantly Black and Hispanic students. Students assigned to the program were over two times more likely to reach the program's target reading level by the end of kindergarten (70% vs. 32%). The results were largely homogenous across student populations and extended to district-administered assessments. These findings provide promising evidence of an affordable and sustainable approach for delivering personalized reading tutoring at scale.
Keywords: I20; I21; I24; I26; 330; high-impact tutoring; literacy gains; randomized control trial